1992
DOI: 10.1007/bf02033057
|View full text |Cite
|
Sign up to set email alerts
|

A seroepidemiologic study of hepatitis a in Spanish children. Relationship of prevalence to age and socio-environmental factors

Abstract: Three child population groups from the Madrid area were studied for anti-HAV antibodies. Analysis was carried out with respect to age and socio-environmental factors. The population understudy was composed of 156 children, with ages ranging from 1 to 14 years; they were stratified in three socio-environmental groups (white-family unit, gypsy-family unit and orphanage), and also divided into subgroups according to age. As a whole, an age-related increase in prevalence was found. The overall seroprevalence by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 4 publications
2
15
0
Order By: Relevance
“…11,20 The association between SES and anti-HAV status in this context has been documented elsewhere in the world as well as in Chile. 10,18,[20][21][22][23] Although ingestion of shellfish or raw shellfish has been found to be associated with HAV, 2,24,25 our data do not support this association after adjusting for age. However, the results of the adjusted analysis, although not significant, are consistent with such an association.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…11,20 The association between SES and anti-HAV status in this context has been documented elsewhere in the world as well as in Chile. 10,18,[20][21][22][23] Although ingestion of shellfish or raw shellfish has been found to be associated with HAV, 2,24,25 our data do not support this association after adjusting for age. However, the results of the adjusted analysis, although not significant, are consistent with such an association.…”
Section: Discussionmentioning
confidence: 74%
“…Residence in areas of lower SES and fewer maternal or paternal years of education were significantly associated with a higher anti-HAV prevalence. HAV infection has been found to be significantly associated with poor hygiene and crowded living situations 2,[16][17][18] as well as with more general measures of SES. 10,19 In the age-stratified analyses, use of potable water, use of a municipal sewage system, use of a toilet/ outhouse, and use of a refrigerator were all significantly associated with anti-HAV serostatus.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate rates of seropositivity are found in the Mediterranean. In Spain, the effect of socioeconomic level is shown by the 63% anti-HAV positive rate among gypsy children aged 1 to 14 years, compared with 46% for children in an orphanage and 23% for nongypsy families (174). In Italy, seropositive rates are higher in the southern part of the country, e.g., 27% anti-HAV positivity in persons aged 3 to 19 years, compared with 5% in northern Italy (235).…”
Section: Why Prevent Hepatitis A?mentioning
confidence: 99%
“…A study in Spain34 found a seroprevalence of HAV antibodies of 82% in deprived Roma children compared with 9.3% of more affluent non-Roma children. In another Spanish study,35 three groups were compared; non-Roma children, Roma children, and children in orphanages. From seven upwards there was an excess in age specific seroprevalence of hepatitis A virus of Roma children over other groups.…”
Section: Resultsmentioning
confidence: 99%